UPAYA MENINGKATKAN MINAT DAN PRESTASI BELAJAR MATEMATIKA DENGAN MENGGUNAKAN PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT(TGT) SISWA KELAS IX C SMP NEGERI 2 KALIWIRO WONOSOBO TAHUN AJARAN 2013/2014 - Awan Prabowo; Benedictus Kusmanto (UNION: Jurnal Ilmiah Pendidikan Matematika, 2016)
The purposes of this research were to increase the student’s interest andachievement in learning mathematics through cooperative learning type TeamGames Tournament (TGT) in 9th grade students of SMP Negeri 2 KaliwiroWonosobo in year 2013/2014. This research was Classroom Action Research(CAR). The subjects in this research were 9th grade students of SMP Negeri 2Kaliwiro Wonosobo. It consists of 29 students. The object of this research werethe student’s interest and achievement of learning mathematic throughcooperative learning type Team Games Tournament (TGT). The results showedthat after the application of Team Games Tournament learning approach, thestudent’s interest and achievement in learning mathematics has increased. Thiscan be shown by an increase in the percentage average questionnaire student’sinterest from 38,95% in pre-cycle to be71,62%in cycle I, and became 78,61% incycle II . The increasing in the percentage average viewed from the observation ofstudent’s interest in learning amounts 66.38% in cycle I became 85.34% in cycleII. The achievement in learning mathematic of students also increased. Judgingfrom the average value of 58.48 in pre-cycle became 64.19 in cycle I, and became80.90 in cycle II. While the percentage of completeness students ( with KKM 70 )also increased, namely the pre-cycle by 31,03% (9 students) were completenessbecame 51,72% (15 students) in cycle I. It increased again became 82.76% (24students) were completeness in cycle II.